Analisis Pengaruh Kualitas Pelayanan, Kualitas Produk, Harga Dan Lokasi Terhadap Loyalitas Pelanggan Melalui Kepuasan Pelanggan Sebagai Variabel Intervening (Studi Pada Pelanggan Warung Kopi Kedai Singgah Malang) - Dwimas Arie Supangkat; Rois Arifin; M. Hufron (UNIVERSITAS ISLAM MALANG, 2020)
AbstractThe purpose of this study was to analyze the effect of service quality, product quality, price and location towards customer loyalty through customer satisfaction as intervening variabel. This research used quantitative methods by collecting the data through questionnaires. The populations in this study were Kedai Singgah coffee shop customers which located at Bendungan Sutami Road, Sumbersari, Lowokwaru, Malang. The sampling technique used accidental sampling. The sample were 93 respondents with a questionnaire collection technique. The data analysis technique in this study used descriptive analysis techniques, tracking analysis and hypothesis testing.The results of this study indicate that the first hypothesis tested service quality; product quality, price and location which directly affect customers’ satisfaction based on the results of the tests that have been carried out that service quality, product quality, price and location affect customers’ satisfaction. The second hypothesis examines the relationship of service quality, product quality, price and location directly affect customers’ loyalty. The third hypothesis examines the relationship of customer satisfaction directly affecting customers’ loyalty. The fourth hypothesis examines the relationship of service quality, product quality, price and location indirectly affect customers’ loyalty through customer satisfaction as the intervening variable. Keywords: Service Quality, Product Quality, Price, Location, Customer Satisfaction, Customer Loyalty